Analisis Rasio Likuiditas, Solvabilitas, Profitabilitas, dan Aktivitas untuk Menilai Kinerja Keuangan Koperasi Sejahtera - Aslama Ramdhani; Elmanizar Elmanizar (Majalah Sainstekes, 2019)
This study aims to determine the financial performance of Sejahtera Cooperative period 2012-2016 measured by aspects of liquidity, solvability, profitability, and activity. This study uses secondary data from financial reports obtained from the Sejahtera Cooperative. This study uses quantitative methods with descriptive format. The results from this study showed cooperative financial performance based on the aspect of likuidity ratio is considered very unhealthy. Cooperative financial performance based on the aspect of solvability ratio is considered healthy. Cooperative financial performance based on the aspect of profitability ratio is considered unhealthy. Cooperative financial performance based on the aspect of activity ratio is considered very unhealthy.